A Novel Electric Vehicle Charging Management With Dynamic Active Power Curtailment Framework for PV-Rich Prosumers - Demirci, Alpaslan; Tercan, Said Mirza; Ahmed, Eihab E. E.; Cali, Umit; Nakir, Ismail (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2024)
Prosumer communities are integrating renewable energy sources to reduce energy costs and carbon emissions for sustainable and clean energy awareness. However, increasing solar photovoltaic penetration in low-voltage distribution networks leads to serious power quality challenges, such as overvoltage for grid operators and prosumers. Integrating electric vehicles (EVs) as deferable loads can reduce prosumer costs and maximize environmental benefits as EV charging is managed. Therefore, this paper proposes a novel EV charging management that maximizes prosumer communities' power quality and benefits PV-rich prosumers by applying a dynamic active power curtailment framework. The methodology calculates each prosumer's maximum power injection into the grid based on their voltage sensitivities. The performance of the developed charging management is examined on the European 906 bus low-voltage distribution networks under unmanaged, managed, and vehicle-to-grid (V2G)-empowered scenarios. The prosumers' individual and aggregated economic cost-benefit results are analyzed considering increasing EV penetration. The results show that the proposed method considering fair active power curtailment could increase self-consumption and renewable fraction for prosumers. It is observed that increasing EV penetration could reduce the curtailed energy by 14.6%. The V2G-empowered method also increased up to 20% more renewable energy for charging EVs, improved self-consumption and renewable fraction up to 11% and 19.4%. Moreover, the V2G option reduced total costs by up to 37.93%. This work can potentially promote renewable energy sources by modifying consumers' charging behaviors to be more sustainable and environmentally friendly.
Keywords: Active power curtailment; vehicle charging management; self-consumption; over-voltage mitigation; sensitivity matrix; IMPACTS; Computer Science; Engineering; Telecommunications